Content Analysis of Palestinian Secondary School Mathematics Textbooks in the Light of the Common Core State Standards for Mathematics CCSSM - Ziada, Rama Ahmad; Qunaibi, Abeer Rushdi (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to analyze the content of Palestinian secondary school mathematics textbooks, which was adopted in the academic year 2019/2020, in the light of the Common Core State Standards for Mathematics CCSSM.The researchers used the descriptive- analytical approach and a content analysis tool, which was prepared based on the CCSSM Standards. The study concluded that mathematics books for the secondary stage in Palestine include the CCSSM for the secondary stage in small percentages, and the books lack a number of standards. One of the most important recommendations of the study is the necessity of informing curriculum specialists about international standards such as the Common Core State Standards for Mathematics (CCSSM) to develop curricula, treat weaknesses, reconsider topics that lack standards in mathematics textbooks for the secondary stage, and enhance strengths.
Keywords: CCSSM Common Core State Standards; mathematics books; content analysis